A Ressourcement Encyclical: Veritatis Splendor and the Recovery of Christocentric Moral Theology - Michael A. Wahl (Journal of Moral Theology)
This article proposes that Pope John Paul II’s _Veritatis Splendor_ is a ressourcement encyclical that creatively retrieves insights from a movement to renew moral theology in a Christo-centric mode which had flourished in the decades immediately preceding Vatican II but dissipated soon after the Council. Although most clearly expressed in its often-neglected first chapter, in fact _Veritatis Splendor_’s Christocentric vision permeates the entire encyclical, including those portions often presumed to be purely philosophical, and lends the encyclical an internal coherence frequently overlooked. Reading _Veritatis Splendor_ as a work of ressourcement and attending to its first chapter as a constructive proposal for moral theology rather than a mere prologue to an analysis of disputed questions offers promising new pathways for receiving the encyclical three decades later.